A Case of Haematometra Secondary to Cervical Stenosis after Vesicle Vaginal Fistula Surgical Repair - Athanase Lilungulu; Willy Mwibea; Mzee Nassoro; Balthazar Gumodoka (Case Reports in Obstetrics and Gynecology)
Background. Haematometra is a rare postobstetrics fistula surgical repair outcome complication; however the condition can be misinterpreted especially in limited resource areas that lack routine ultrasound guidance and with a slowly progressed increase in size of abdomen accompanied with a history of amenorrhoea together with a history of having unprotective sexual intercourse which may increase the possibility of being controversial to full-term gravid uterus. The causes of haematometra might be either due to congenital abnormality of the vaginal canal or acquired iatrogenically. However, any other cause that involved vaginal canal can be a predisposing factor of haematometra. We present a case of a 32-year-old female patient, who had obstetric fistula which was successfully repaired over the past two years. She presented with one-year-and-two-month history of an amenorrhoea that was progressive accompanied with distended abdomen to the extent of looking typically as the gravid uterus. Explorative laparotomy was performed successfully and surgical incision managed by hysterotomy and salpingotomy, whereby approximately ten liters of serosanguinous blood fluid mixed with blood clots was completely suctioned. Despite being a rare condition after vesicle vaginal fistula repair complication outcome, haematometra remains to be relatively common gynaecological condition among female adolescence during postpubertal period.